Effects of bismuth oxide on the properties of calcium phosphate bioceramics - W., H. Yeo; Singh, Ramesh; Tan, Chou Yong; Aw, K. L.; Ranna, Tolouei; H., Kelvin; Iis, Sopyan; Teng, Wan Dung; Hoque, Md Enamul (Trans Tech Publications, Switzerland, 2011)
The aim of this work is to study the phase stability and sinterability of bismuth oxide (Bi2O3) doped HA ranging from 0.05 wt% to 1 wt%. The green samples were sintered in air at temperature ranging from 1000oC to 1400oC. In this experiment, the results from XRD analysis revealed that the stability of HA phase was disrupted when addition of 0.3, 0.5 and 1.0 wt% Bi2O3 were used and when samples sintered above 1100oC, 1000oC and 950oC, respectively. In general, HA containing 0.5 wt% of Bi2O3 and when sintered at 1000oC was found to be beneficial in enhancing densification, Young’s modulus, Vickers hardness and fracture toughness. Throughout the sintering regime, the highest value of relative bulk density of 98.7% was obtained for 0.5 wt% Bi2O3-doped HA when sintered at 1000oC. A maximum Young’s modulus of 119.2 GPa was observed for 0.1 wt% Bi2O3-doped HA when sintered at 1150oC. Additionally, 0.5 wt% Bi2O3-doped HA was able to achieve highest hardness of 6.04 GPa and fracture toughness of 1.21 MPam1/2 at sintering temperature of 1000oC. Furthermore, the Young’s modulus of HA was found to vary linearly with bulk density.